2000
DOI: 10.1046/j.1440-1681.2000.03198.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Dietary Fibre Improves Insulin Sensitivity By Increasing Muscle Glut‐4 Content In Stroke‐Prone Spontaneously Hypertensive Rats

Abstract: 1. The effects of soluble dietary fibre (psyllium) on peripheral insulin sensitivity and skeletal muscle GLUT-4 protein expression were studied in 12 male stroke-prone spontaneously hypertensive rats (SHRSP) fed a high-caloric diet from 5 to 9 weeks of age. 2. In the psyllium-supplemented group, fasting plasma glucose was significantly reduced and glucose levels following an oral glucose tolerance test were significantly lower than in the cellulose-supplemented group at 30 (P < 0.05) and 60 min (P < 0.01). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 34 publications
1
35
0
3
Order By: Relevance
“…During lactation, insulin resistance is negatively correlated with the feed intake of sows (Van der Peet-Schwering et al, 2004;Mosnier et al, 2010). Several studies have shown that soluble dietary fiber can improve insulin sensitivity in mice or rats (Song et al, 2000;Isken et al, 2010). The inclusion of KF in gestation diet increased the level of SF in present study (Table 1).…”
Section: Discussionsupporting
confidence: 52%
“…During lactation, insulin resistance is negatively correlated with the feed intake of sows (Van der Peet-Schwering et al, 2004;Mosnier et al, 2010). Several studies have shown that soluble dietary fiber can improve insulin sensitivity in mice or rats (Song et al, 2000;Isken et al, 2010). The inclusion of KF in gestation diet increased the level of SF in present study (Table 1).…”
Section: Discussionsupporting
confidence: 52%
“…Difficulties investigating signalling pathways in the liver are another problem in human studies. Several relatively short-term studies in animal models reported soluble fiber such as guar gum or psyllium being superior in improving insulin sensitivity, in comparison to insoluble cellulose [11,12]. In a study investigating male Wistar rats, short-term feeding with guar gum vs. cellulose or bran had favourable effects on body weight and carbohydrate tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the diabetes death rate in England decreased by approximately 55% between 1941 and 1954-1957, when low-fibre white flour was replaced by the wartime high-fibre national flour [10]. Acute effects of dietary fibres have been studied extensively, the focus of interest being soluble, viscous fibres, which can delay gastric emptying [11] and the absorption of macronutrients from the gut [12], influencing lipid metabolism, postprandial glycaemic responses to carbohydrate-rich meals [13] and insulin sensitivity in rat muscles [14]. However, in population studies soluble fibres are not associated with a decreased risk of type 2 diabetes or cardiovascular disease [3,4,7,15].…”
Section: Introductionmentioning
confidence: 99%